THE ROLE AND PLACE OF INNATE AND ACQUIRED IMMUNITY IN THE REGENERATION OF LONG-TERM NON-HEALING WOUNDS AGAINST THE BACKGROUND OF DIABETES MELLITUS - Aripova, T.U.; Umarov, B.Y. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The physiological process of wound healing includes four stages: hemostasis, inflammation, proliferation, and maturation. The correct and coordinated work ensures a strict staged regenerative process. However, when wounds do not go through this organised process, their healing is delayed, and this eventually leads to chronic or long-lasting wounds. Common signs of non-healing wounds are exudation, reinfection, tissue necrosis, defective re-epithelialization, decreased angiogenesis, and excess production of reactive oxygen species. In general, chronic wounds can be divided into three main categories: diabetic foot ulcers, vascular ulcers, and pressure ulcers. They are usually observed in elderly people suffering from pathological conditions such as diabetes mellitus, vascular diseases and obesity. This review article is devoted to the features of the reaction of innate and acquired immunity in the course of long-term non-healing wounds.